Strategic Affection? Gift Exchange in Seventeenth-Century Holland - Thoen, Irma (Solidarity and Identity, 2006)
Gifts, from objects to hospitality and from poems to support, are a means of establishing and maintaining social ties. This study focuses on the nature of seventeenth- century Dutch social relations through the exchange of gifts by a wide range of individuals, from schoolmaster and artisan to poet and regent. Their gift-exchange behaviour is compared to contemporary gift exchange to show that both strategy and affection are necessary elements of social relations at any given time, and that what changes most is not the system but the discourse of exchange.